PENGARUH JIWA KEWIRAUSAHAAN MASYARAKAT TERHADAP KEBERHASILAN BUMDES PERTANIAN - Amzallova, Vignansia (Berkala Ilmiah AGRIDEVINA, 2020)
An organization was founded because it has a goal to be achieved. This can be achieved with an entrepreneurial spirit. BUMDES is a village business organization that is managed by the community and village government. The establishment of BUMDES aims to drive local economic development at the village level, formed based on the needs, capacity, potential of the village and increasing the economic level of village communities. Rural areas cannot be separated from the agricultural sector. The agricultural sector plays an important role as a food producing sector. The factors that influence the entrepreneurial spirit are: self-confidence, initiative, motivation, leadership, courage to take risks, and human relationships. The existence of BUMDES Ngadeg Jejeg in agriculture needs to be developed so that it can empower local people to achieve prosperity. Research Objectives (1.) To determine the influence of entrepreneurial factors in the agricultural BUMDES community. (2.) Knowing the influence of the role of the entrepreneurial spirit on the success of the BUMDES Agriculture community. This study uses quantitative methods, namely data collection using research instruments. The collected data were analyzed using statistics to determine the validity test, reliability test, and normality test. Then processed with Structural Equation Modeling (SEM) in order to test the hypothesis. Sampling using random sampling. Data collection techniques, namely: interviews, observation, documentation, literature study, and questionnaires. The sample taken in this study was ≥100 respondents in Meger village, Ceper district, Klaten Regency. The results showed that human relations and initiative had a positive effect on entrepreneurial spirit and was accepted at a significant level of 5%. The role of the entrepreneurial spirit has a positive effect on the success of BUMDES Ngadeg Jejeg, Meger village, Ceper district, Klaten district can be accepted at a significant level of 5%. DOI : https://doi.org/10.33005/adv.v9i2.2463